Islamic microfinance: A review of the emerging agricultural market in the ASEAN market - Dimvy Rusefani Asetya (PRIVIETLAB, 2025)
Islamic microfinance presents a burgeoning opportunity to address financial exclusion among millions of impoverished Muslims by providing financial services. This paper explores the intersection of Islamic microfinance with the agricultural market in the ASEAN region, where smallholder farmers constitute a significant demographic. While the potential of Islamic microfinance to empower farmers and promote sustainable practices is acknowledged, there remains a gap in understanding its tailored implementation and impact within the ASEAN agricultural context. By synthesizing existing literature, this review underscores the need for further research to elucidate the specific mechanisms, challenges, and impacts of Islamic microfinance in supporting agricultural development and poverty alleviation in ASEAN countries.